An in vivo study on the metabolism and osteogenic activity of bioabsorbable Mg–1Sr alloy. (1st January 2016) - Tie, Di; Guan, Renguo; Liu, Huinan; Cipriano, Aaron; Liu, Yili; Wang, Qiang; Huang, Yuanding; Hort, Norbert
Graphical abstract: Abstract: Previous studies indicated that local delivery of strontium effectively increased bone quality and formation around osseointegrating implants. Therefore, implant materials with long-lasting and controllable strontium release are avidly pursued. The central objective of the present study was to investigate the in vivo biocompatibility, metabolism and osteogenic activity of the bioabsorbable Mg–1Sr (wt.%, nominal composition) alloy for bone regeneration. The general corrosion rate of the alloy implant as a femoral fracture fixation device was 0.55 ± 0.03 mm · y −1 (mean value ± standard deviation) in New Zealand White rabbits which meet the bone implantation requirements and can be adjusted by material processing methods. All rabbits survived and the histological evaluation showed no abnormal physiology or diseases 16 weeks post-implantation. The degradation process of the alloy did not significantly alter 16 primary indexes of hematology, cardiac damage, inflammation, hepatic functions and metabolic process. Significant increases in peri-implant bone volume and direct bone-to-implant contact (48.3% ± 15.3% and 15.9% ± 5.6%, respectively) as well as the expressions of four osteogenesis related genes (runt-related transcription factor 2, alkaline phosphatase, osteocalcin, and collagen, type I, alpha 1) were observed after 16 weeks implantation for the Mg–1Sr group when compared to the pure Mg group. The sound osteogenic properties of the Mg–1Sr alloy by long-lasting and controllable Sr release suggesting a very attractive clinical potential. Statement of significance: Sr (strontium) has exhibited pronounced effects to reduce the bone fracture risk in osteoporotic patients. Nonetheless, long-lasting local Sr release is hardly achieved by traditional methods like surface treatment. Therefore, a more efficient Sr local delivery platform is in high clinical demand. The stable and adjustable degradation process of Mg alloy makes it an ideal Sr delivery platform. We combine the well-known osteogenic properties of strontium with magnesium to manufacture bioabsorbable Mg–1Sr alloy with stable Sr release based on our previous studies. The in vitro and in vivo results both showed the alloy's suitable degradation rate and biocompatibility, and the sound osteogenic properties and stimulation effect on bone formation suggest its very attractive clinical potential.